2010
DOI: 10.1115/1.4001128
|View full text |Cite
|
Sign up to set email alerts
|

Transient Temperature Data Analysis for a Supersonic Flight Test

Abstract: Determination of transient surface heat flux from the temperature data is one of the traditional techniques applied in many engineering applications. With respect to high speed flight experiments, the time scale of measured temperature data is usually very small (∼ms). So, one-dimensional heat conduction analysis is expensively used to infer surface heating rates on the body. For an analytical modeling, it is necessary to obtain a closed form solution from experimentally measured temperature data. In this pape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 11 publications
1
13
0
Order By: Relevance
“…It has been proposed by several researchers that the substrate body dimension of TFG is to be chosen in such a way to consider it as semi-infinite body along with the assumptions that measured surface temperature at stagnation point (point ‘M’ as shown in Figure 7) on thin film is same as that of substrate surface and heat transfer through rear end of the substrate is negligible, while substrate thermal properties throughout the experiment remains constant (Schultz and Jones, 1973; Taler, 1996). In order to predict the heat flux at stagnation point ‘M’, the instantaneous surface temperature data recorded at ‘M’ is fed to the simplified expression of the solution of one dimensional heat conduction problem for semi-infinite body as shown in equation (3) (Sahoo and Kumar, 2016; Sahoo and Peetala, 2010; Schultz and Jones, 1973, Taler, 1996). The quantity within square root outside the bracket in numerator in equation (3) is collectively termed as effective thermal product of the substrate.…”
Section: Experimental and Numerical Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…It has been proposed by several researchers that the substrate body dimension of TFG is to be chosen in such a way to consider it as semi-infinite body along with the assumptions that measured surface temperature at stagnation point (point ‘M’ as shown in Figure 7) on thin film is same as that of substrate surface and heat transfer through rear end of the substrate is negligible, while substrate thermal properties throughout the experiment remains constant (Schultz and Jones, 1973; Taler, 1996). In order to predict the heat flux at stagnation point ‘M’, the instantaneous surface temperature data recorded at ‘M’ is fed to the simplified expression of the solution of one dimensional heat conduction problem for semi-infinite body as shown in equation (3) (Sahoo and Kumar, 2016; Sahoo and Peetala, 2010; Schultz and Jones, 1973, Taler, 1996). The quantity within square root outside the bracket in numerator in equation (3) is collectively termed as effective thermal product of the substrate.…”
Section: Experimental and Numerical Analysismentioning
confidence: 99%
“…A number of existing numerical techniques are available to evaluate the value of heat flux from equation (3). It has been observed that trapezoidal and Simpson rule of approximation methods have limitations owing to the existence of singularity condition at the upper limit, t=τ, while piecewise linear approximation method evades this problem and results obtained through this method are more accurate with less computational time (Cook, 1970; Sahoo and Peetala, 2010). In the present work cubic spline method is used for discretization purpose to deduce the heat flux values from transient temperature histories.…”
Section: Experimental and Numerical Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…These investigations for small time scales of a few milliseconds (ms), can be related to the experimental testing for heat transfer measurements in ground‐based impulse facilities (e.g., shock tunnels) because the typical test duration of these facilities ranges from a few hundred microseconds to a couple of milliseconds . In such facilities, the most preferred measurement technique is the prediction of surface heat flux from temperature signals with appropriate heat conduction modeling . These short duration temperature signals are acquired from thin film sensors consisting of a sensing element and substrate material.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, the gauge is treated as thin film or thick film gauge for which heat transfer models will be different . The Conventional CFD studies reported in the open literature do highlight the methods for determination of wall heat flux and support the experimental investigations . However, such methods have limitation on the prediction of wall temperature and heat flux that are claimed to be accurate for short duration time scale of measurements.…”
Section: Introductionmentioning
confidence: 99%